Histopathological and Histochemical Effects of Chloropyriphos on the Renal and Hepatic Tissues of Albino Rat - Saha, AK; Afroz, Rokshana; Mahanta, MK; Laz, Rezina (Bangladesh Journal of Genetics and Biotechnology, 2009)
Key words: Chloropyriphos; liver; kidney; histopathology; rat Bangladesh j. genet. biotechnol. 7(1&2): 61-64 2006 (June & December)